2013
DOI: 10.1007/s12630-013-9994-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the anesthesiologist in the wider governance of healthcare and health economics

Abstract: Purpose Healthcare resources will always be limited, and as a result, difficult decisions must be made about how to allocate limited resources across unlimited demands in order to maximize health gains per resource expended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
6
0
6
Order By: Relevance
“…20 In this way, best practices can be defined among anesthesia departments based on the measurement of both cost and evidence-based benefit. In our study, we observed a decrease in cost with minimal changes in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…20 In this way, best practices can be defined among anesthesia departments based on the measurement of both cost and evidence-based benefit. In our study, we observed a decrease in cost with minimal changes in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…If value is the goal, the most relevant question when choosing between anesthetic drugs is whether the most expensive agents provide a margin of benefit that is worthy of the additional cost. 1 Meta-analyses found no difference in clinical or resource outcomes when comparing desflurane, dexmedetomidine, or remifentanil with active comparators. 6 - 14 Many of the proposed statistically significant benefits of more costly anesthetic agents, such as faster emergence from anesthesia, do not translate into clinically important benefits in terms of real reductions in morbidity and resource utilization.…”
Section: Value Rather Than Costmentioning
confidence: 98%
“…To appreciate cost containment initiatives, we need to understand the foundational metrics of health economics: cost-minimization, cost-effectiveness, cost-utility, and cost-benefit analysis. 1 In particular, we need to understand that costs and cost analyses are not bona fide health economic analyses since they provide just one side of the equation, i.e., costs only. In healthcare, costs alone are not enough; we are often willing to pay increasingly more for increasingly better outcomes.…”
Section: Role Of Health Economic Analysismentioning
confidence: 99%
See 2 more Smart Citations